Kazakhstan, tourism - Sarmento, João Carlos Vicente (2022)
Kazakhstan is the 9th largest country in the world (2.7 million km2), and the largest landlocked country. Located in Central Asia (Figure 1), with a population of 18.5 million (2019) it is bordered by Russia, Uzbekistan, Kyrgyzstan, Turkmenistan and China. Its economy is dependent on oil and gas (over 35% GDP and nearly 75% of total exports in 2019), and is world’s largest uranium producer (Pomfret, 2019).